The effect of brain dominance on the relationship between learning styles and Japanese language academic achievement - Wei, H. S.; Sulaiman, Tajularipin (Southeast Asian Association for Institutional Research, 2018)
Languages have become an important tool in the borderless global communication and interaction. A significant increase in the number of foreign language learners has been recorded and the research of Japanese teaching and learning has significantly increased. However, teaching and learning Japanese Language is a challenge because students learnt differently. This study aimed to explore the mediation effect of Left-brain and Right-brain Dominance on the relationship between Learning Styles and Japanese Language Academic Achievement. The results showed that Left-brain and Right-brain Dominance had full mediation effect on the relationship between Learning Styles and Japanese Language Academic Achievement. The effect of Left-brain Dominance on Japanese Language Academic Achievement was statistically significant at 0.001 level with the standardized effects of 0.245. Whereas the effect of Right-brain Dominant on Japanese Language Academic Achievement was statistically significant at 0.001 level with the standardized effects of 0.258. The results showed that four sub-constructs of learning styles were the indicators for Japanese language learning. However, these Learning Styles did not significantly influence a student’s Japanese language academic achievement due to its weak effect i.e. 0.041 in terms of its relationship strength. The Left-brain and Right-brain Dominance has an impact on individuals’ learning styles whereby the activities in the brain halves could overtake Japanese language learning. In any case, the consideration of the strategies of Learning Styles, Left-brain and Right-brain learning strategies would enhance the results of Japanese Language Academic Achievement.